Surgical management of primary parapharyngeal space tumors: a 10-year review. (3rd June 2017) - Shi, Xiaoling; Tao, Lei; Li, Xiaoming; Wu, Haitao; Huang, Weiting; Chen, Xiaoling; Li, Cai; Shen, Yan; Chen, Qi; Tang, Di; Wei, Chunsheng; Wang, Dehui; et al.
Abstract: Conclusions: Most neoplasms of the parapharyngeal space are benign. The transcervical surgical approach is the preferred procedure in most cases. Intra-operative endoscopic exploration offers a new surgical management technique to reduce operative complications and post-operative recurrence rates. Objectives: To present the authors' experience in the treatment of primary parapharyngeal space tumors with emphasis on surgical approaches and employment of endoscopy to detect residual tumors through conventional approaches. Method: One hundred and sixty-seven patients treated surgically over a 10-year period were retrospectively reviewed. A comparison of the surgical approaches in a relevant case series was also conducted. Results: All of the patients underwent pre-operative imaging before surgery, and intra-operative endoscopic detection was selectively used for large, deep tumors. Complete resection of the tumor was used in 158 patients (95%), with a transcervical surgical approach applied in 144 cases (84%). Of 167 tumors, 150 (90%) were benign and 17 (10%) were malignant, with neurilemmoma/schwannoma as the most frequent pathology (42%). Surgical complications were reported in 26 patients (15%), most commonly unilateral paralysis of the vocal cords (6%). Two patients (1%) presented with recurrence, on average 2.5 years (range = 1–4 years) after initial excision, and the mean follow-up time was 3.8 years (range = 10 months–10 years).